Response of imidazolinone-resistant and -susceptible weedy rice populations to imazethapyr and increased atmospheric CO2 - B. Piveta,Leonard (2020)
Abstract Background: Weedy rice (Oryza sativa L.) is the main weed of rice crop. The high genetic variability of weedy rice contributes to the high phenotypic diversity between biotypes and different responses to environmental stress. Objective: The present study aimed to evaluate the response of imidazolinone-susceptible and -resistant weedy rice populations to increased atmospheric [CO2]. Methods: The experiment was arranged in a complete randomized design with six replications. The treatments included two [CO2] concentration (700 and 400 μmol mol-1) and three treatments: resistant genotype (IMI-resistant) treated with imazethapyr; resistant genotype without imazethapyr, and a susceptible genotype without imazethapyr. Results: The IMI-resistant and -susceptible weedy rice responded similarly to [CO2] enrichment. Enhanced [CO2] increased competitive ability of the weedy rice populations tested, by means of increased plant height. Weedy rice seed production also increased with enhanced [CO2] by means of increased photosynthesis rate and reduced transpiration (increased water use efficiency). Increased seed production also means increased weed persistence as it increases the soil seedbank size. The application of imazethapyr on IMI-resistant weedy rice did not alter its response to [CO2]; conversely, increased [CO2] did not change the resistance level of weedy rice to imazethapyr. High [CO2] increased spikelet sterility, but this beneficial effect was negated by the overall increase in production of filled grains. Conclusions: Enhanced [CO2] concentrations increases weedy rice growth, photosynthesis rates, seed production and spikelet sterility; the imidazolinone application does not affect the response of weedy rice to enhanced [CO2] affects weedy rice response to imidazolinone herbicide.